CORPORATE GOVERNANCE AND VOLUNTARY HUMAN CAPITAL DISCLOSURE IN THE LISTED COMPANIES OF BANGLADESH: A CONCEPTUAL OVERVIEW - Shamem Ara Mili; Fathyah Hashim (International Journal of Accounting, Finance and Business, 2020)
Human capital disclosure provides information on companies’ human capitaldevelopment initiatives, employees’ current benefits, and their future safety. Higher level ofhuman capital (HC) disclosure might be able to make the employees more pleased andmotivated. However, good corporate governance (CG) makes sure professional ethics inbusiness, and functions in favour of the interest of diverse stakeholders of the business. HCdisclosure is voluntary in Bangladesh, and hence, corporate governance mechanisms (CGMs)could play an important role to disclose more HC information. Similarly, from the agencytheory standpoint, HC disclosures reduce information asymmetry, and thus, HC disclosurescould minimize the agency conflicts associated with the business. The aim of the paper is tointegrate pertinent empirical researches and literature to extend the potentials of CG attributesto amplify HC disclosures of the listed firms in Bangladesh. In addition, the paper will presenttheoretical base for future empirical investigation to expand the agency theory explanationregarding the association of CG with HC disclosures. Moreover, extant literature providesinconsistent and less evidence regarding the rapport of CG with HC disclosures. The presentpaper recommends and illustrates potential propositions for future empirical study. It isexpected that the empirical investigations on these propositions would endow with knowledgeto investors, practitioners, and policy makers regarding upgrading voluntary HC disclosure bymeans of superior corporate governance.